2017
DOI: 10.2527/jas.2016.1002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of dietary energy source and body weight gain during the juvenile period on metabolic endocrine status and age at puberty in beef heifers1

Abstract: Using a previously established model for nutritional acceleration of puberty, beef heifers ( = 48; 1/2 Angus × 1/4 Hereford × 1/4 Brahman) were used in a replicated 2 × 2 factorial design to examine the effects of diet type (high forage [HF] vs. high concentrate [HC]) and rate of BW gain (low gain [LG], 0.45 kg/d, vs. high gain [HG], 0.91 kg/d) on key metabolic hormones and age at puberty. After weaning at 14 ± 1 wk of age, heifers were assigned randomly to be fed HC-HG, HC-LG, HF-HG, or HF-LG ( = 12/group) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The age at puberty in Holstein calves is, on average, 250 days (8.3 mo), with approximately 30% of the calves reaching puberty as early as at 7 mo [25]. The Angus, a beef breed, reaches puberty at about 13 mo [26]. Conversely, our calves attained puberty at an average of 20.5 mo, consistently with the age previously reported by others for the Nelore breed [18].…”
Section: Discussionsupporting
confidence: 89%
“…The age at puberty in Holstein calves is, on average, 250 days (8.3 mo), with approximately 30% of the calves reaching puberty as early as at 7 mo [25]. The Angus, a beef breed, reaches puberty at about 13 mo [26]. Conversely, our calves attained puberty at an average of 20.5 mo, consistently with the age previously reported by others for the Nelore breed [18].…”
Section: Discussionsupporting
confidence: 89%
“…In female offspring of malnourished fathers, oocyte meiotic competence was reduced, expression of glucose transporters in ovaries and cumulus cells was altered, and reproductive ability was compromised, as seen by lower fertilization and cleavage rates as well as embryos with delayed development (Ashworth et al, 2009). In cattle production systems, bulls are commonly placed on high-energy rations during development to result in a high rate of weight gain (Allen et al, 2017). Energy expenditure during the breeding season commonly results in weight loss in bulls, especially in bulls that have not reached their mature body weight and are still undergoing post-pubertal reproductive maturation (Cardoso et al, 2014).…”
Section: The Effects Of Parental Environmental Exposure On Epigeneticmentioning
confidence: 99%
“…The important effects of nutrition controlling the reproductive neuroendocrine system and pubertal progression in heifers have been well established. Previous experiments conducted by our group ( Cardoso et al ., 2014a , b; Allen et al ., 2017 ) and others ( Gasser et al ., 2006a ) have demonstrated that increasing nutrient intake during the juvenile period can markedly advance the timing of puberty in beef heifers. In studies performed by Gasser et al .…”
Section: Impact Of Nutrition On Pubertal Developmentmentioning
confidence: 99%